Nursing Care for Chronic Disease - Sukmawati, Sukmawati (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study investigates the implementation and impact of evidence-based practices (EBPs) in nursing care for chronic diseases, focusing on their effectiveness, variability across healthcare settings, and the role of training and professional development. Research Design and Methodology: This research employs a mixed-methods design, integrating quantitative and qualitative approaches. A cross-sectional survey gathered data from nurses, patients, and healthcare administrators across urban and rural settings. In-depth interviews and focus group discussions provided qualitative insights. The sample included 300 participants for the survey and 50 for qualitative analysis. Data were analyzed using both descriptive and inferential statistics, as well as thematic analysis. Findings and Discussion: The study found that evidence-based practices (EBPs) significantly improve patient outcomes in managing chronic diseases, including diabetes, hypertension, and COPD. However, variability in EBP implementation was noted, particularly between urban and rural healthcare settings, due to differences in resources and support. The research highlighted the critical need for comprehensive training and continuous professional development among nurses. These findings support the hypothesis that EBPs enhance patient outcomes and align with theoretical frameworks such as the Chronic Care Model. Implications: This study contributes to scientific knowledge and practical application by providing robust evidence on the benefits and challenges of EBPs. The findings underscore the importance of targeted training programs and fostering an organizational culture of continuous learning. Future research should focus on longitudinal studies and strategies to overcome barriers to EBP adoption in resource-limited settings.